Mechanical high-intensity focused ultrasound creates unique tumor debris enhancing dendritic cell-induced T cell activation - van den Bijgaart, Renske J. E.; Mekers, Vera E.; Schuurmans, Fabian; Raaijmakers, Tonke K.; Wassink, Melissa; Veltien, Andor; Dumont, Erik; Heerschap, Arend; Fütterer, Jurgen J.; Adema, Gosse J. (Frontiers in Immunology, 2022)
In situ tumor ablation releases a unique repertoire of antigens from a heterogeneous population of tumor cells. High-intensity focused ultrasound (HIFU) is a completely noninvasive ablation therapy that can be used to ablate tumors either by heating (thermal (T)-HIFU) or by mechanical disruption (mechanical (M)-HIFU). How different HIFU ablation techniques compare with respect to their antigen release profile, their activation of responder T cells, and their ability to synergize with immune stimuli remains to be elucidated. Here, we compare the immunomodulatory effects of T-HIFU and M-HIFU ablation with or without the TLR9 agonist CpG in the ovalbumin-expressing lymphoma model EG7. M-HIFU ablation alone, but much less so T-HIFU, significantly increased dendritic cell (DC) activation in draining lymph nodes (LNs). Administration of CpG following T- or M-HIFU ablation increased DC activation in draining LNs to a similar extend. Interestingly, ex vivo co-cultures of draining LN suspensions from HIFU plus CpG treated mice with CD8+ OT-I T cells demonstrate that LN cells from M-HIFU treated mice most potently induced OT-I proliferation. To delineate the mechanism for the enhanced anti-tumor immune response induced by M-HIFU, we characterized the RNA, DNA and protein content of tumor debris generated by both HIFU methods. M-HIFU induced a uniquely altered RNA, DNA and protein profile, all showing clear signs of fragmentation, whereas T-HIFU did not. Moreover, western blot analysis showed decreased levels of the immunosuppressive cytokines IL-10 and TGF-β in M-HIFU generated tumor debris compared to untreated tumor tissue or T-HIFU. Collectively, these results imply that M-HIFU induces a unique context of the ablated tumor material, enhancing DC-mediated T cell responses when combined with CpG.